Produção e caracterização de material de referência de forrageira para nutrientes e contaminantes inorgânicos - Bossu, Carla Maíra (2013)
The main aim of this work was to produce a candidate material for national reference material, the forage Brachiaria brizantha Stapf. cv. Marandu, containing known levels of contaminants (Cr, Pb, Cd, and As) and macro and micronutrients (Ca, P, Mg, K, Cu, Fe, Mn, Zn and Na). Brachiaria brizantha Stapf cv. Marandu was shown in 400 pots containing 25 kg of soil. The pots were kept in a greenhouse at Embrapa Southeast Livestock located in Sao Carlos, SP. A previous study was conducted in order to establish an appropriate concentration of contaminants that would not harm the dry matter production critically. In order to produce a reference material containing inorganic contaminants in its structure, the dose of 25 mmol/pots was chosen and added into 375 pots. The first harvest occurred after approximately 60 days of plant growth, and the second one after 120 days. Then, the samples were oven-dried at 45°C for 72 hours and grounded first in a cutting mill and then in an ultra-centrifugal mill to reduce particle size. It was produced 20 kg of dried and grounded material. After this, the homogenization and other processes were carried out, including packaging and gamma irradiation dosage in the range of 5-10 kGy to increase the shelf life. Other relevant studies were also undertaken, such as: particle size distribution, betweenbottles and within-bottle homogeneity evaluation, short and long term stability tests using ICP-MS techniques for As, Cd, Cr and Pb, and ICP OES for Ca, P, Mg, K, Cu, Fe, Mn , Zn and Na. Relative humidity and homogeneity between-bottles were also carried out using INAA. All tests presented results within the range of 95%, assuring homogeneity and stability of the candidate material for forage reference material. The consensus values for the 13 elements were determined by collaborative program. All these experiments were performed in accordance with the ISO Guides 30 to 35.